Dr. DETERMINATION AND MODELING OF ULTIMATE TENSILE STRENGTH OF BREADFRUIT PEEL-LOW DENSITY POLYETHYLENE (BRFP-LDPE) COMPOSITE APPLYING BIGG’S EQUATION - Rabboni, Dr. Government; Ayuba, Dr. Solomon (INSTEP Network, 2024)
(LDPE) for breadfruit peel-low density polyethylene composite using statistical means to model ultimate tensile strength of the BRFP-LDPE composite using Bigg’s model. The breadfruit peel at fraction of 0.5-.0.25 wt when it was not modified was blended with LDPE matrix (UNT). The BRFP was later modified with NaOH (NST), NaOH+CH3COOH (AAT),, NaOH+CH3COOH+MAPE (MPT) impregnated in LDPE matrix to manufactured BRFP-LDPE composite by injection molding machine, respectively. After production, BRFP-LDPE composite was tested for the ultimate tensile strength. The results show that the Bigg’s model was able to give the prediction of the maximum tensile strength of BRFP-LDPE composite with coefficient of correlation (R2M) for the model =0.994 for UNT, NST, AAT and MPT, respectively. Also, in the same vein, the coefficient of correlation as derived from the experiments (R2) were 0.975, 0.978, 0.8 and 0.955 for the tensile strength of BRFP-LDPE composite which coincided for UNT, NST, AAT and MPT, respectively.. Finally, the relative percentage deviation modulus between experiment and Bigg’s equation (µ) <10. These statistical data seen confirmed highly prediction of ultimate tensile strength of experimental values using the Bigg”s model.